DIALOG TOLERANSI ANTAR UMAT BERAGAMA - Riza Firdaus, Luthfi (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
Religious diversity called for harmonious dialogue. Diversity was a reality that exists and is part of the nation's personality. This article aimed to analyse different concepts of inter-religious dialogue. The article presented the basis of dialogue, religious harmony and models of interreligious dialogue. This research used a qualitative approach. The method was a literature review.  The data collection technique was content analysis. The research found that in order to achieve meaningful and productive interfaith dialogue, it is important to build trust, demonstrate openness, and commit to mutual understanding and respect. Religious dialogue should recognise that despite differences in beliefs and practices, there is also a common mission to promote social justice, peace and goodness in the world. Interfaith cooperation can strengthen efforts to address global challenges such as poverty, climate change and conflict. Interfaith dialogue requires a strong awareness of the differences between religious beliefs. This includes recognition and appreciation of the uniqueness and diversity of existing religions.